Upaya Membangun Sikap Moderasi Beragama Mahasiswa melalui Pembelajaran Agama Islam Berbasis Masalah - Najib, Khotim Hanifudin; Hidayatullah, Ahmad Syauqi; Widayat, Prabowo Adi (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2022)
The Indonesian nation is known as a pluralistic nation (religion, culture, language, customs). The plurality of the nation brings two consequences, namely strength, and conflict. Become a strength if the Indonesian people are able to accept pluralism, and becomes a conflict if they cannot accept pluralism. Of course, we all hope that this plurality will become the strength of the nation. Therefore, it is necessary to build the strength of this nation with its plurality. One of the efforts that can be done to build the strength of religious communities is to build an attitude of religious moderation. Efforts to build students’ religious moderation can be done in various ways, one of which is through problem-based learning. The purpose of this study is to reveal the problem-based learning of the Islamic Religion as an effort to build students’ religious moderation attitudes in public universities. The research method used is qualitative with a phenomenological approach and survey. The subjects of this study were Universitas Sarjanawiyata Tamansiswa students from the faculty of teacher training and education in the Islamic Religion course. Data is collected through observation, documentation, and questionnaires. The research was conducted by observing Islamic religious learning and strengthening it by studying learning documents. The results show that problem-based Islamic learning can shape students' religious moderation attitudes.